2015
DOI: 10.1155/2015/456353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sintering Mechanism on the Properties of ZrO2 Reinforced Fe Metal Matrix Nanocomposite

Abstract: The present paper reports phase, microstructure, and compressive strength of ZrO 2 reinforced Fe Metal Matrix Nanocomposites (MMNCs) synthesized by powder metallurgy (P/M) technique. High purity grade iron metal powder was mixed with varying percentage of zirconium dioxide (5-30 wt%), compacted, and sintered in argon atmosphere in the temperature range of 900-1100 ∘ C for 1 to 3 hours. X-ray diffraction (XRD) analysis of specimens was done in order to study the phases present and scanning electron microscopy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It is observed that iron zirconium oxide depends on the sintering temperature and time. 11 Gupta et al studied fabrication of iron (Fe)aluminium oxide (Al 2 O 3 ) metal matrix composite by powder metallurgy technique at different sintering temperature and corrosion behaviour of the composite material by electrochemical method. 12 Garg et al studied the effect of sintering temperature on the structural and mechanical behaviour of Al-Graphene composite.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that iron zirconium oxide depends on the sintering temperature and time. 11 Gupta et al studied fabrication of iron (Fe)aluminium oxide (Al 2 O 3 ) metal matrix composite by powder metallurgy technique at different sintering temperature and corrosion behaviour of the composite material by electrochemical method. 12 Garg et al studied the effect of sintering temperature on the structural and mechanical behaviour of Al-Graphene composite.…”
Section: Introductionmentioning
confidence: 99%
“…Jha et al. 7 showed that ZrO 2 when added as a reinforcement with Fe metal leads to improved yield strength and compressive modulus due to higher percentage of ZrO 2 . Sharma et al.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, researchers have reported the mechanical and wear properties of various ceramic-reinforced Fe-based metal matrix composites processed using P/M. 710 Gupta et al 11 observed that wear rate of Fe-Al 2 O 3 metal matrix composites was dependent on the sintering temperature and time. Adhesive wear was found to be dominant at lower load, while abrasive wear was instrumental at higher load.…”
Section: Introductionmentioning
confidence: 99%